Cartilage. Volume 3, - Grässel, Susanne; Aszódi, Attila (Springer, 2017)
In three Volumes this mini book series presents current knowledge and new perspectives on cartilage as a specialized yet versatile tissue. This third volume provides insight into current and future treatment strategies for repair of cartilage lesions. This book addresses Professors, researchers and PhD students who are interested in musculoskeletal and cartilage pathobiology and tissue-engineering.
Keywords: Cartilage.; Cartilage -- Regeneration.; elektronické knihy; electronic books